APPLICATION OF TEACHERS BASIC TEACHING SKILLS IN MATHEMATICS LEARNING - Midun Haris (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Education is an activity in an effort to improve human resources in a better direction in improving personal quality through the teaching and learning process. There are several subjects studied in elementary school, one of which is mathematics. Mathematics is a very important subject for students to understand, because mathematics is a compulsory subject at all levels of education. Students' low understanding of mathematics material cannot be separated from the role of the teacher. Teachers are professional educators whose main task is to teach and educate students. In carrying out their duties, teachers are required to apply 8 basic teaching skills. namely skills in opening and closing lessons, explanation skills, questioning skills, class management skills, small group guiding skills, small group and individual teaching skills, variety providing skills, and reinforcement skills. This research was carried out from September 11 to September 20. The data collected is data regarding the application of teachers' basic teaching skills in class II mathematics learning. The results of the research regarding basic teaching skills in homeroom teachers, on the skill of providing variations from the 5 indicators observed, namely 4 that appeared, on the skill of asking from 5 indicators, namely 4, on the skill of giving reinforcement from 5, namely 4 appeared.